Pengenalan Pendidikan dan Profesi Tenaga Kesehatan Rumah Sakit pada Siswa SMA Guna Mengembangkan Wawasan Dunia Karir - Dina Fitriana R; Rawi Miharti (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Higher education is one of the stakeholders which have a role in preparing quality productive age through Tri Dharma. The success of preparing a generation at the senior high school level will be able to support Indonesia's success in 2030. It is expected that with age, energy and great enthusiasm it will become a big capital for the country's development. The purpose of this activity is to encourage the growth of student awareness in planning further education or career as a description of future life plans and to increase knowledge about the insights of female students related to education and the health professionals especially in complex hospitals. The method in implementing this activity is by counseling, discussion and question and answer. The activity was held on Friday, 11 August 2017 at 1:00 p.m. - 3:00 p.m. WIB at SMA (Senior High School) 2 Wates in Kulon Progo Yogyakarta. The introduction of education and the profession of the health workforce in the form of explanatory counseling was attended by 131 students of SMA N 2 Wates who were students of class XII majoring in Science and Social Sciences at SMA N 2 Wates. This activity took place by involving several parties, namely the lecturer and student team of Medical Record Study Program, headmaster and counseling teacher (BK) as well as class XII students at SMA N 2 Wates in Kulon Progo. The participants took part in the activity well, actively and enthusiastically.